Fish Parasites and Heavy Metals Relationship in Wild and Cultivated Fish as Potential Health Risk Assessment in Egypt - Radwan, Mahmoud; Abbas, Mahmoud Mahrous M.; Afifi, Moharam Adel Mohamed; Mohammadein, Amaal; Al Malki, Jamila S. (Frontiers in Environmental Science, 2022)
Despite wide studies of biomonitoring aquatic environment through dynamics of host-parasite exist, bio-indicators to track the influence and accumulation of heavy metals on fish are still few. The present study sheds light on the relation between fish parasites and heavy metal as it threatens the fish health and, as a consequence, that of human after fish consumption. Samples of Nile tilapia (Oreochromis niloticus) were collected in Burullus Lake, a wild fish source, and from a private fish farm in Kafr El-Sheikh Governorate, in Egypt. They were exposed to various pollutants associated with anthropogenic activities to determine the levels of accumulation of Fe, Zn, Cu, beside the top three most toxic metals (As, Cd, and Pb), in water and fish tissues of gills, intestine, liver and muscles in both wild and farmed O. niloticus. The results showed the order of abundance: Fe < Zn < Pb < Cu < As < Cd. In waters of both farmed and wild fish, there was a significant negative relation between parasite prevalence and heavy metals, including Zn, Pb, and As. Also, there was a significant positive relation between parasite prevalence with Cu while no significant relation was found with Fe and Cd. Heavy metal content was significantly higher (p > 0.05) in non-infected than infected farmed and wild O. niloticus. In addition, a significantly decreased concentration (p > 0.05) of essential heavy metal was recorded in wild fish compared to farmed specimens, while non-essential heavy metal was significantly higher (p > 0.05) in wild compared to farmed fish. Bioaccumulation factors (BAF) of different organs of O. niloticus were ranked in ascending order: Liver > Gills > Intestine > Muscles. In general, the risk assessment showed safe human consumption for farmed and wild fish under the reported environmental conditions in this study. Moreover, parasites presence can be adopted as surrogate indicator to estimate the potential impact of heavy metal pollution and accumulation.